Surface Treatment and Application in Acrylic Polyurethane Coating of Nano-Scale ZnO Powders - Wang, Dongzhi; Ge, Heyi (Asian Journal of Chemistry, 2012)
In this paper, the nano-scale ZnO powders were prepared by sol-gel method and modified with toluene diisocyanate (TDI). The modified nano-scale ZnO powders can disperse in acrylic polyurethane coating homogenously. The dispersion stabilization of modified ZnO powders in acrylic polyurethane coating was significantly improved in comparison with the as-prepared ZnO powders, which was due to the introduction of grafted polymers by surface treatment. The ultraviolet absorption ability of nano-scale ZnO powders were tested by UV spectrophotometer, when the modified nano-scale ZnO powders are added into the acrylic polyurethane coating. The addition amount of ZnO powders improve and the ultraviolet absorption ability.